Britain and the Arctic - Depledge, Duncan (Springer International Publishing, 2018)
British interest in the Arctic has returned to heights not seen since the end of the Cold War; concerns about climate change, resources, trade, and national security are all being impacted by profound environmental and geopolitical changes happening in the Arctic. Duncan Depledge explores why it seems to have taken until now for Britain - once an 'Arctic state' itself - to notice how close it is to these changes, what its contemporary interests in the region are, and whether the British government's response in the arenas of science, defence, and commerce is enough. He investigates the increasing geopolitical significance of the Arctic, providing an overview of Britain's historical connections to the Arctic. This book will be of interest to both academics and practitioners seeking to understand contemporary British interest and activity in the Arctic. .